This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let y = x + k. Then (x + k)^3 - y^3 = y(y + k) + 61.Expanding and re-arranging, (3k - 1)y^2 + (3k^2 - k)y = 61 - k^3. This shows that possibilities for k are limited to 1,2, or 3. If k = 3, 8y^2 + 24y = 34, obviously no solution; if k = 2, 5y^2 + 10y = 53, again no solution. For k = 1, 2y^2 + 2y = 60, or y^2 + y = 30, and y = 5; then x = 6, and x^3 - y^3 = 91 = 5*6 + 61. Ed Gray